Local Antioxidant Status in Patients with Keratoconus after Ultraviolet Corneal Crosslinking - A. R. Khalimov; L. I. Khalimova; E. L. Usubov (Oftalʹmologiâ, 2019)
The article presents the study results of the local antioxidant status in patients with progressive keratoconus and its dynamics after the ultraviolet corneal crosslinking. Purpose: to study the oxidative activity in the tear of the patients with keratoconus and its dynamics after ultraviolet cornea crosslinking. Patients and methods. To assess the local level of oxidative activity in keratoconic patients according to the levels of total antioxidant status (TAS) and superoxide dismutase (SOD) in the tear fluid, as well as their dynamics after UV crosslinking were investigated. The study included 38 patients (38 eyes) with keratoconus stage I–II (classification according to Amsler), men — 24 (63.1 %), women — 14 (36.9 %). The standard UV crosslinking group (S-CXL) was 20 eyes, and the pulsed accelerated protocol (I-CXL) — 18 eyes. The average age of patients was 32.4 ± 6.8 years. As a control group, 12 practically healthy individuals were selected. The time of observation is before the operation, on the 3rd, 7th, 14th and 30th days after the procedure. Results: On the basis of the conducted studies, it was revealed that keratoconus patients showed a statistically significant decrease in the initial indicator of TAS by 40 % and amounted to 1.68 ± 0.21 mmol/l, compared to healthy people — 2.82 ± 0.15 mmol/l. The SOD level in tears in patients with keratoconus was also lower by 19 % — to 96.7 ± 11.3 ng/ml, compared to the control — 119.1 ± 16.5 ng/ml. The use of S-CXL of the cornea caused a decrease in TAS during the first 3 days with the subsequent restoration of its level. The use of pulse A-CXL also showed a decrease in this indicator, but by the end of 1st month the level of TAS was higher than preoperative and better than when using the standard protocol. A decrease in SOD level after treatment was noted during the first 3 days, however, the use of S-CXL caused a more significant collapse of this indicator compared to the pulsed accelerated corneal crosslinking protocol. Conclusion. TAS data and SOD level had shown a decrease in local antioxidative status in patients with keratoconus. Ultraviolet corneal crosslinking causes the maximum decrease in SOD and TAS on the 3rd day after the procedure, and from the 14th day their gradual recovery to the initial level is observed. The standard protocol contributed to a more pronounced development of local cross-linking damage in patients with keratoconus. It manifests itself in the antioxidant status reduction of the tear compared to the pulsed accelerated method.